Legal knowledge and economic development : the case of land rights in Uganda - Yamano, Takashi (Policy research working paper, 2006)
"Mixed evidence on the impact of formal title in much of Africa is often used to question the relevance of dealing with land policy issues in this continent. The authors use data from Uganda to assess the impact of a disaggregated set of rights on investment, productivity, and land values, and to test the hypothesis that individuals' lack of knowledge of the new law reduces their tenure security. Results point toward strong and positive effects of greater tenure security and transferability. Use of exogenous knowledge of its provisions as a proxy for the value of the land law suggests that this piece of legislation had major economic benefits that remain to be fully realized. "--World Bank web site